REKONSTRUKSI METODOLOGI PENDIDIKAN ISLAM PADA ERA ARTIFICIAL INTELLIGENCE: INTEGRASI HUMAN INTELLIGENCE DAN MACHINE INTELLIGENCE - Ina Damayanti; Ramdanil Mubarok (STAI Sangatta Kutai Timur, 2026)
This study aims to reconstruct the methodology of Islamic education in the era of Artificial Intelligence through the integration of Human Intelligence, Machine Intelligence, and Islamic values. The study uses a qualitative approach with library research, analyzed through thematic analysis, conceptual analysis, and theoretical synthesis of Islamic education literature, Artificial Intelligence in Education (AIEd), and Human–Machine Intelligence studies. The results show that AI cannot replace the fundamental function of Islamic education because it lacks spiritual awareness, moral responsibility, empathy, and role models. However, AI can act as a learning assistant, knowledge enhancer, and cognitive partner that strengthens learning effectiveness. This study produces a reconstruction model called the Integrative Islamic Intelligence Methodology. This model reconstructs educational goals, learning resources, the role of teachers, learning methods, and evaluation systems through the development of four main dimensions: Spiritual Intelligence, Ethical Intelligence, Critical Intelligence, and Technological Intelligence. These findings confirm a paradigm shift from knowledge transmission to an intelligence integration paradigm, which places humans at the center of developing values, morality, spirituality, and wisdom, while AI serves as an instrument for strengthening intellectual capacity in achieving the goals of holistic Islamic education.